Heterocyclic Aromatic Amines in Cooked Meat Products: Causes, Formation, Occurrence, and Risk Assessment - Gibis, Monika (Comprehensive reviews in food science and food safety, 2016)
Meat products are sources of protein with high biological value and an essential source of other nutrients, such as vitamins and minerals. Heating processes cause food to become more appetizing with changes in texture, appearance, flavor, and chemical properties by the altering of protein structure and other ingredients. During heat treatment, heterocyclic aromatic amines (HAAs), potent mutagens/carcinogens, are formed due to the Maillard reaction. The HAAs are classified in at least 2 groups: thermic HAAs (100 to 300 °C) and pyrolytic HAAs (>300 °C). This review focuses on the parameters and precursors which affect the formation of HAAs: preparation, such as the marinating of meat, and cooking methods, including temperature, duration, and heat transfer, as well as levels of precursors. Additionally, factors are described subject to pH, and the type of meat and ingredients, such as added antioxidants, types of carbohydrates and amino acids, ions, fat, and other substances inhibiting or enhancing the formation of HAAs. An overview of the different analytical methods available is shown to determine the HAAs, including their preparation to clean up the sample prior to extraction. Epidemiological results and human daily intake of HAAs obtained from questionnaires show a relationship between the preference for very well‐done meat products with increased HAA levels and an enhanced risk of the incidence of cancer, besides other carcinogens in the diet. The metabolic pathway of HAAs is governed by the activity of several enzymes leading to the formation of DNA adducts or HAA excretion and genetic sensitivity of individuals to the impact of HAAs on human cancer risk.